Evaluation of a pilot of nurse practitioner led, GP supported rural palliative care provision. Issue 1 (December 2016) - Mitchell, Geoffrey; Senior, Hugh; Bibo, Michael; Makoni, Blessing; Young, Sharleen; Rosenberg, John; Yates, Patsy
Abstract Background Providing end of life care in rural areas is challenging. We evaluated in a pilot whether nurse practitioner (NP)-led care, including clinical care plans negotiated with involved health professionals including the general practitioner(GP), ± patient and/or carer, through a single multidisciplinary case conference (SMCC), could influence patient and health system outcomes. Methods Setting – Australian rural district 50 kilometers from the nearest specialist palliative care service. Participants: Adults nearing the end of life from any cause, life expectancy several months. Intervention- NP led assessment, then SMCC as soon as possible after referral. A clinical care plan recorded management plans for current and anticipated problems and who was responsible for each action. Eligible patients had baseline, 1 and 3 month patient-reported assessment of function, quality of life, depression and carer stress, and a clinical record audit. Interviews with key service providers assessed the utility and feasibility of the service. Results Sixty-two patients were referred to the service, forty from the specialist service. Many patients required immediate treatment, prior to both the planned baseline assessment and the planned SMCC (therefore ineligible for enrollment). Only six patients were assessed per protocol, so we amended the protocol. There were 23 case conferences. Reasons for not conducting the case conference included the patient approaching death, or assessed as not having immediate problems. Pain (25 %) and depression (23 %) were the most common symptoms discussed in the case conferences. Ten new advance care plans were initiated, with most patients already having one. The NP or RN made 101 follow-up visits, 169 phone calls, and made 17 referrals to other health professionals. The NP prescribed 24 new medications and altered the dose in nine. There were 14 hospitalisations in the time frame of the project. Participants were satisfied with the service, but the service cost exceeded income from national health insurance alone. Conclusions NP-coordinated, GP supported care resulted in prompt initiation of treatment, good follow up, and a care plan where all professionals had named responsibilities. NP coordinated palliative care appears to enable more integrated care and may be effective in reducing hospitalisations.